Modified MPPT based Grid Connected Solar PV System with Improved Power Quality - P, Mammuthu; Gopalakrishnan, V. (Journal of Electrical Engineering and Automation, 2022)
The power demand in the world is growing at a drastic rate. Two drivers that stimulate energy consumption are emerging countries’ technological economic progress and population increase. Photovoltaic energy generation is one of the most environmental friendly methods of energy creation. PV systems have recently seen an increase in demand due to the fact that they create electricity without harming the environment by directly converting solar energy into electricity. PV works at its highest power point, which is dependent on irradiance and temperature, to attain maximum efficiency. Since solar irradiance and solar temperature fluctuate over time, a photovoltaic system capable to track the MPP must be designed to generate more energy. This project introduces a novel solar panel control method known as Maximum Power Point Tracking (MPPT), wherein the suggested technique employs Variable Step Size P&O (VSS P&O) MPPT to enhance the transient responsiveness. The step size is automatically adjusted with respect to the point of operation. Simulations utilising MATLAB/ Simulink software are used to assess the suggested method’s performance.